Rat tissue reaction to MTA FILLAPEX (R) - Gomes Filho, João Eduardo [UNESP]; Watanabe, Simone [UNESP]; Lodi, Carolina Simonetti [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Nery, Mauro Juvenal [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Dezan Junior, Eloi [UNESP]; Bernabé, Pedro Felício Estrada [UNESP] (Wiley-Blackwell, 2012)
The aim of this study was to evaluate the rat subcutaneous tissue reaction to implanted polyethylene tubes filled with mineral trioxide aggregate (MTA) FILLAPEX (R) compared to the reaction to tubes filled with Sealapex (R) or Angelus MTA (R). These materials were placed in polyethylene tubes and implanted into the dorsal connective tissue of Wistar rats for 7, 15, 30, 60, and 90 days. The specimens were stained with hematoxylin and eosin or Von Kossa or left unstained for examination under polarized light. Qualitative and quantitative evaluations of the reaction were performed. All materials caused moderate reactions after 7 days, which decreased with time. The reactions were moderate and similar to that evoked by the control and Sealapex (R) on the 15th day. MTA FILLAPEX (R) and Angelus MTA caused mild reactions beginning after 15 days. Mineralization and granulation birefringent to polarized light were observed with all materials. It was concluded that MTA FILLAPEX (R) was biocompatible and stimulated mineralization.